2014
DOI: 10.4018/irmj.2014070102
|View full text |Cite
|
Sign up to set email alerts
|

English Abstracts in Open Access Translation Studies Journals in Spain (2011-12)

Abstract: In this study of 197 abstracts from the ten most prestigious open access Translation Studies journals published in Spain between 2011-12, 73 of 197 abstracts (37%) were found to contain a total of 128 errors (75 grammatical, 42 vocabulary-related and 11 typographical). Three “risk factors” were suspected to correlate with higher error incidence (>40% error rate), namely: 1. when abstracts do not conform to the author's guidelines for language and length; 2. when abstracts appear in monographic issues or dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Unlike Klimova (2013), Linder (2014) investigated the quality of 197 published English abstracts selected from Spain’s ten most prestigious open-access translation studies journals. Although the overall quality of these abstracts was much better than what Klimova (2013) had reported, the results indicated that 73 English abstracts contained 128 grammatical, vocabulary-related, and typographical errors.…”
Section: A Brief Narrative Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike Klimova (2013), Linder (2014) investigated the quality of 197 published English abstracts selected from Spain’s ten most prestigious open-access translation studies journals. Although the overall quality of these abstracts was much better than what Klimova (2013) had reported, the results indicated that 73 English abstracts contained 128 grammatical, vocabulary-related, and typographical errors.…”
Section: A Brief Narrative Literature Reviewmentioning
confidence: 99%
“…Unlike Klimova (2013) and Linder (2014) who investigated the quality of actual abstracts written by EFL researchers, Hosseingholipour et al (2021) examined the perceptions of nine physical education professors and four Ph.D. students at Iranian universities about the factors affecting the quality of Iranian researchers’ English abstracts as well as their common errors in writing English abstracts. The results indicated that problems with the English language negatively affect the quality of Iranian researchers’ English abstracts; and English language errors were commonly committed by them.…”
Section: A Brief Narrative Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If a leave or other causes are delayed, the manuscript will not arrive at the editor's hand, which will affect the timeliness of the manuscript processing. In view of this reason, our editorial department was launched in March 2016 by Chinese HowNet to provide "periodical collaborative editing system", the author at the time of submission must enter my print online submission system, and the real name registration, complete manuscript Abstract keywords English translation, author information, contact information and a series of information, and the need for accurate selection of manuscript categories after uploading articles attachments [8]. When the editors of related columns log on to the contributor system with their own accounts, they can see the author's contribution for the first time, and have detailed author information and contact information.…”
Section: The Networking Of the Processing Mode Of The Object Of Editimentioning
confidence: 99%
“…. An indication of this internationalization, at least within Europe, is an article which studies the English abstracts of Translation Studies articles published in Spanish, pointing to the need to produce coherent versions summaries for international readers(Linder, 2014).…”
mentioning
confidence: 99%